A self-phonological analysis on my english pronunciation as an indonesian efl learner - Salsabila, Hanum - (Maliki Interdisciplinary Journal, 2025)
This study addresses the problem of pronunciation errors frequently encountered by English as a Foreign Language (EFL) learners, which can affect both confidence and communicative effectiveness. The aim of this research is to analyze the patterns of pronunciation errors made by the author as an EFL learner and to identify the underlying causes. The study employs Error Analysis (EA) to map the errors and Generative Phonology to explain the phonological mechanisms behind them. Data were collected from the pronunciation of 40 English words recorded through the SpeechAce application and analyzed using a descriptive-quantitative approach. The findings reveal that substitution errors dominate (89.8%), followed by elision (10.2%), with no distortion detected. The most frequent errors occurred in the phonemes /k/, /ə/, /t/, /s/, and /p/. Further analysis indicates that errors arise not only from first language transfer but also from articulatory limitations, such as difficulty in controlling tongue movement. This highlights that pronunciation learning requires an integrative approach that encompasses cognitive, linguistic, and physiological aspects. In conclusion, this study emphasizes that understanding EFL learners’ phonological errors should account for both linguistic and non-linguistic factors and underscores the importance of reflective and supportive pronunciation teaching strategies.